Alteration of differentiation and growth of normal human epidermal keratinocytes by benzo[a]pyrene and arsenic - Perez, Damon Scott, author; Campain, Julie, advisor; Yang, Raymond Shih-hsien, 1940-, advisor; Legare, Marie E., committee member; Fox, Michael, committee member; Ranu, Rajinder S., committee member (Colorado State University. Libraries, 2005)
Normal human epidermal keratinocytes (NHEK) were chosen as an in vitro model for mechanistic studies into how altered regulation of differentiation may play a role in the malignant transformation process in human cells. Initially, the cytotoxicity of four petroleum-derived hydrocarbons [benzo[a]pyrene (BaP), carbazole, dibenzothiophene, and isoquinoline] was investigated using the MTT assay; however, the research direction changed to focusing on examining the cellular effects, in NHEK, of BaP, the most toxic and carcinogenic polycyclic aromatic hydrocarbon among the four, and arsenic, another high priority skin carcinogen. This work demonstrates that BaP and arsenic inhibit terminal differentiation in NHEK. Arsenic also decreases proliferation in a manner suggestive of a G2 block. In contrast, BaP increases proliferation rates and induces rapid progression through the cell cycle, possibly by a shortened G2 phase. Differentiation is more sensitive to chemically-mediated perturbations than is proliferation, indicating that the former process may be the initial target at environmentally prevalent concentrations. To identify molecular alterations that are responsible for the observed chemical-specific effects, microarray analysis was carried out on NHEK treated with each carcinogen. From this analysis, BaP and arsenic altered 103 and 122 genes respectively. More sensitive real-time PCR revealed that BaP-treatment perturbed the expression of genes involved in cellular differentiation and growth. Altered genes include; α-integrin binding protein-63, interleukin-1α, interleukin-1β, Ras guanyl releasing protein-1, retinoic acid- and interferon-inducible protein, and YY1-associated factor-2. Arsenic altered the expression of genes involved in cell cycle checkpoint regulation. These genes include; MAX binding protein, RAD50, retinoblastoma-1, retinoblastoma-binding protein-1, and transforming growth factor β-stimulated protein. Gene expression results suggest that BaP and arsenic target different steps in the pathways to growth and differentiation in this cell type and provide mechanistic clues as to how these chemicals favor transformation in target cells. Moreover, a quantitative biologically-based computer model of NHEK was developed providing an in silico experimental platform with which one can test chemical-mediated effects on cell cycle kinetics and differentiation. A clearer understanding of cellular growth and differentiation, both from a normal standpoint and from alterations induced by chemical exposure, will greatly aid the risk assessment process for environmental contaminants.
Keywords: arsenic; normal human epidermal keratinocytes; NHEK; benzo[a]pyrene; BaP; Carcinogenicity testing; Keratinocytes; Arsenic; Benzopyrene